Novel poly herbal muco-adhesive formulation for treatment of oral aphthous ulcer - Sahu, Rimjhim; Jain, Deepika; Mehani, Rekha; ., Hemani; Hingorani, Lal; Thawani, Vijay (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Oral ulcers are the most frequent lesions that cause discomfort for which the patients seek treatment for alleviating pain and facilitate early healing. Various treatment modalities from modern medicine and Ayurveda are used in the form of ointments and mouthwashes with varying efficacy. Anti-inflammatory medicines, enzymatic preparations, gamma globulins and immune suppressants have been used. Methods: Extracts of five chosen herbs, Glycyrrhiza glabra, Acacia catechu, Punica Granatum, Curcuma longa and Mentha piperita were used for preparing mucoadhesive gel for the treatment of oral aphthous ulcers of any etiology. Gel was prepared by cold method of Schmolka at M/s Pharmanza Herbals Pvt. Ltd., India. Five formulations were prepared with using different concentration of active pharmaceutical ingredient (API) extracts. Results: Formulations were analyzed for different physical and chemical properties. Preliminary trial was done with five formulations. The F5 formulation has the premier viscosity because of its higher polymer content; it is able to remain on mucous surface long enough to release its API effect. Since the uniformity, proper appearance, stability and acceptable viscosity and gel strength the F1 formulation was selected as the superior formulation which could prove ideal for treatment of oral aphthous ulcers. Conclusions: The results provide strong evidence that polyherbal gel containing extracts of Glycyrrhiza glabra, Acacia catechu, Punica granatum, Curcuma longa and Mentha piperita on the basis of their analgesic, anti-inflammatory, antioxidant, wound healing, antimicrobial and local anesthetic properties can be used as an effective and safe alternative for the management of aphthous ulcers.